Truth of the physis and social lie: Doktor Glas, a failed Übermensch? (ACME, 2022)
This study investigates the points of contact between the German philosopher Friedrich Nietzsche and the Swedish writer Hjalmar Söderberg in the latter’s novel Doktor Glas. The paper examines two Nietzschean texts hitherto little related to Söderberg’s work, i.e.: Über Wahrheit und Lüge im außermoralischen Sinne and Die fröhliche Wissenschaft, highlighting the influences that the German philosopher’s thought exerted on the conception of Doktor Glas. The analysis starts from the concepts of lie and knowledge as formulated in Über Wahrheit und Lüge im außermoralischen Sinne and from the concept of “death of God”, recognizing in the latter the collapse of metaphysics in the European philosophical thought starting from the Copernican Revolution. The essay illustrates how this change has resulted in the development of a new technical-scientific sensitivity linked to the sphere of physis, a change that sees the figure of the doctor as its highest representative. The article therefore highlights how in Doktor Glas the transition from metaphysics to physis is represented as a moment of existential crisis, since the doctor does not have the ability to overcome the trauma of the loss of metaphysics. This inability is caused by knowledge, which, while offering the possibility of discovering the lies used by society, does not however allow humanity to find the stimulus to overcome the condition of emptiness caused by the “death of God”. Söderberg therefore provides in his novel a pessimistic interpretation of the crisis of Fin de siècle and understands in Dr. Tyko Gabriel Glas’ inner paralysis and in the futile murder of Pastor Gregorius the failure of the passage from the metaphysical paradigm to the paradigm of physis and the impossibility of overcoming the crisis through a metamorphosis into the condition of Übermensch.
Keywords: Übermensch; Nietzsche; Söderberg; physis; medicine; metaphysics